SUV39H1 regulates corneal epithelial wound healing via H3K9me3-mediated repression of p27 - Shuai Yang; Weiwei Chen; Shanshan Jin; Guangying Luo; Xia Jing; Qi Liu; Peter S. Reinach; Jia Qu; Dongsheng Yan (Eye and Vision, 2022)
Abstract Background Corneal epithelial wound healing (CEWH) is vital for maintaining the integrity and barrier function of the cornea. Although histone modifications mediating gene expression patterns is fundamental in some other tissues, it remains unclear whether these gene regulation patterns underlie CEWH. Suppressor of variegation 3-9 homolog 1 (SUV39H1) plays a vital role in mediating gene silencing via histone H3 trimethylation of lysine 9 (H3K9me3). This study aims to characterize the comprehensive signature of epigenetic modifiers and determine the role of SUV39H1 in CEWH. Methods NanoString nCounter technology was used to detect the differentially expressed epigenetic modifiers during CEWH. Bioinformatic analyses were performed to reveal their involvement in this process. After knockdown of SUV39H1 with siRNA transfection, we determined the function of SUV39H1 on cell proliferation and migration in human corneal epithelial cells (HCECs) via MTS, EdU, and wound-healing assay, respectively. Flow cytometry analysis further confirmed the effect of SUV39H1 on the cell cycle of HCECs. Loss-of-function assays for SUV39H1 with siRNA injection or chaetocin assessed the role of SUV39H1 on CEWH in vivo. Quantitative reverse transcription polymerase chain reaction (RT-qPCR) and Western blotting characterized the expression of SUV39H1 and its target genes. Chromatin immunoprecipitation assay was used to evaluate the distributions of H3K9me3 marks at the promoters of SUV39H1 target genes. Results We first identified 92 differentially expressed epigenetic modifiers and revealed their involvement during CEWH. SUV39H1 was confirmed to be upregulated in response to corneal injury. Its downregulation significantly inhibited HCEC proliferation and retarded in vivo CEWH. Furthermore, knockdown of SUV39H1 upregulated the p27 expression level and reduced H3K9me3 marks at p27 promoter in HCECs. In addition, p27 was remarkably downregulated with elevated H3K9me3 marks at its promoter during in vivo CEWH. Conclusions SUV39H1 plays a critical role in regulating corneal epithelial cell proliferation via H3K9me3-mediated suppression of p27 during CEWH. Our findings suggest that epigenetic modifiers such as SUV39H1 can be potential therapeutic approaches to accelerate corneal repair.